Alien. Romulus [videorecording (Blu-Ray)] - Alvarez, Fede, 1978-; Sayagues, Rodo; Spaeny, Cailee, 1997-; Jonsson, David, 1993-; Renaux, Archie, 1997-; Merced, Isabela, 2001-; Fearn, Spike E.; Wu, Aileen; Wallfisch, Benjamin; Olivares, Galo (20th Century Studios, 2024)
While scavenging the deep ends of a derelict space station, a group of young space colonizers come face to face with the most terrifying life form in the universe.